A modified Delphi study of structures and processes related to medicines management for elderly hospitalised patients in the United Arab Emirates. Issue 5 (8th April 2016) - Al Shemeili, Saeed; Klein, Susan; Strath, Alison; Fares, Saleh; Stewart, Derek
Abstract: Rationale and aim: The structures and processes around the management of medicines for elderly, hospitalized patients are ill defined. This study aimed to determine consensus related to strategic and operational approaches in the United Arab Emirates. Methods: A modified Delphi technique, consensus study with first round statements developed from systematic reviews related to medicines management. Normalization process theory and the theoretical domains framework were applied in the construction of statements, organized into key elements of medicines management: guidelines for medicines management, medicines reconciliation, medicines selection, prescribing and review, medicines adherence, medicines counselling, health professional training and evaluation research. Seventy per cent (summative agree and strongly agree) was set as the target for consensus. Thirty panellists were recruited, representing senior physicians working within geriatrics, hospital pharmacy and nursing directors, chief health professionals (including social workers) and policy makers within the Health Authority of Abu Dhabi and academics. Results: A high level of consensus was obtained for most statements relating to the structures and processes of medicines management. While consensus was not achieved for targeting only those patients with medicines related issues, it was achieved for focusing on all elderly admissions. Similarly, consensus was not achieved for which professions were most suited to roles but was achieved for trained and competent staff. Conclusions: High levels of consensus were obtained for structures and processes of medicines management relating to elderly hospitalized patients. Trained and competent health professionals were preferred to specific professions for any tasks and that all elderly patients and not targeted patients should be the focus for medicines management.